Overview of solutions in quantum information technologies, part 3 - Czarnacki, Łukasz; Kowalczyk, Hubert; Krawiec, Marcin; Misiejuk, Jagna; Ciepielewski, Jan; Szczepaniak, Jakub; Mielczarek, Kacper; Romaniuk, Ryszard S. (International Journal of Electronics and Telecommunications, 2026)
This paper presents the third installment in a series reviewing contemporary solutions in quantum information technologies. Seven thematic areas are surveyed: (1) quantum control engineering, covering theoretical foundations, open-loop and feedback architectures, and industrial optimization use cases; (2) quantum radar, examining quantum illumination principles alongside the fundamental power and decoherence barriers to practical deployment; (3–4) the integration of quantum technologies with embedded systems and the Internet of Things, including quantum random number generators, nitrogen-vacancy magnetometers, miniaturized atomic clocks, and post-quantum cryptographic protocols such as QKD; (5) quantum simulation, contrasting analog and digital approaches with an emphasis on recent large-scale experiments demonstrating quantum utility; (6) quantum haptic interfaces for education, molecular simulation, and research visualization; and (7) quantum entanglement theory, tracing the path from the EPR paradox through Bell’s theorem to the 2022 Nobel Prize. Across these domains, the paper identifies recurring engineering challenges — particularly decoherence, scalability, and the transition from laboratory demonstrations to industrial deployment — and highlights the growing convergence of quantum physics with control theory, embedded computing, and applied engineering.